The Economic Performance of Indonesian Rice-based Agribusiness - Mariyono, Joko (UI Scholars Hub, 2014)
Inefficiency is one of major causes of low performance in Indonesian rice production. This study measures the technical efficiency of rice production in five Indonesian regions and examines its determining factors. A stochastic frontier production function is used to reflect best practice production given certain levels of input use with equal amounts of technology. Unbalanced panel data on input-output rice production consisting of 358 farm operation in 2003, 2008 and 2013 are employed for estimating frontier production functions. The results indicate that variation in rice production across the five main regions is due primarily to variation in technical efficiency. Sources of variation within technical inefficiency include household characteristics, composition of labour and tractor use. Of the five regions investigated, rice production on Java is the most efficient. Technical efficiency of rice production increases over time in all five regions but remains low overall. This study concludes that there is considerable room for productivity improvements in Indonesian rice-based agribusiness through increases in technical efficiency.